Flight initiation distance of Eurasian tree sparrow (Passer montanus) across residential vegetation gradients in Bogor, West Java, Indonesia - SENO NUR ROHMAN; ANI MARDIASTUTI; YENI ARYATI MULYANI (Society for Indonesian Biodiversity, 2025)
Abstract. Rohman SN, Mardiastuti A, Mulyani YA. 2025. Flight initiation distance of Eurasian tree sparrow (Passer montanus) across residential vegetation gradients in Bogor, West Java, Indonesia. Biodiversitas 26: 6188-6196. Birds inhabiting urban areas must adapt to coexist with humans in order to survive. Exposure to human activities may threaten their presence, as anthropogenic stimuli often trigger behavioral reactions similar to those induced by predators, such as moving away when approached. This anti‑predator behavior represents an adaptive response indicating vigilance and can be quantitatively measured using Flight Initiation Distance (FID) to assess bird tolerance to human disturbance. This study aimed to examine the tolerance of Eurasian tree sparrows (Passer montanus) in three residential areas of Bogor, West Java, Indonesia, with differing vegetation density and canopy cover. In total, 120 individuals were recorded across vegetation density categories: high (n = 46), medium (n = 36), and low (n = 38). The data were analyzed using non‑parametric methods because the distribution was not normal, applying the Kruskal-Wallis test followed by Dunn’s post hoc analysis. The results revealed significant differences in FID across sites (p<0.05). FID values increased with vegetation density: 2.82±0.77 m (low), 4.22±1.57 m (medium), and 6.24±2.09 m (high). These results indicate that Eurasian tree sparrows exhibit greater tolerance in urban environments with lower vegetation density and canopy cover, highlighting their resilience and adaptability to human-dominated habitat changes. By situating these findings in a tropical urban context, this study contributes baseline data to a region where behavioral ecology remains underrepresented.